Audit Tata Kelola Sistem Informasi Pemerintahan Daerah (SIPD) Menggunakan Framework COBIT 5 (Studi Kasus Pada BAPPEDA Provinsi Jawa Barat) - Jayanti, Rima; Supriatna, Iyeh (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
The implementation of this application is due to the replacement of Permendagri No. 77 of 2020 concerning regional financial management which has replaced the previous Permendagri namely Article 391 paragraph (1) of Law No. 23 of 2014 concerning Regional Government which is the legal basis for BAPPEDA of West Java Province in implementing the Local Government Information System (SIPD) to assist regional financial management so that it can run effectively and efficiently. This study aims to find out the current maturity level (IT Maturity Level) of the current SIPD governance. This research is applied research with qualitative research methods based on a case study approach. For determining the maturity level of SIPD governance, this research uses the scoring method. The governance audit in this study was conducted using the COBIT 5 Framework by selecting IT Processes in all EDM, APO, BAI, DSS, and MEA domains. The result of measuring the maturity of SIPD governance at BAPPEDA of West Java Province is 2.88 at level 2 in the